Visible light sensitive photoinitiating systems: Recent progress in cationic and radical photopolymerization reactions under soft conditions. (February 2015) - Xiao, Pu; Zhang, Jing; Dumur, Frédéric; Tehfe, Mohamad Ali; Morlet-Savary, Fabrice; Graff, Bernadette; Gigmes, Didier; Fouassier, Jean Pierre; Lalevée, Jacques
Abstract: Although there have been many reports on photoinitiating systems adapted to visible lights for radical photopolymerization, the challenge for the design and development of photoinitiating systems for cationic photopolymerization or concomitant radical/cationic photopolymerization (for interpenetrating polymer network IPN synthesis) with visible lights still remains open. Particularly, the recent development of cheap and easily accessible LEDs operating upon soft visible light irradiations has opened new fields for polymer synthesis. Since 2011, many novel photoinitiating systems based on organic and organometallic compounds with excellent visible light absorption have emerged and exhibited outstanding photoinitiating abilities especially for cationic photopolymerization. In this review, recent progress (mainly from 2011 to early 2014) in applications of photoinitiators and sensitive photoinitiating systems under visible lights are reported. In addition, their relative efficiencies in the photopolymerization of different monomers are exemplified and discussed.